First record of cannibalism in the Lima leaf-toed gecko, Phyllodactylus sentosus (Reptilia, Phyl-lodactylidae) - Valdez, Fernando (2017)
We report a case of cannibalism for the Lima leaf-toed gecko, Phyllodactylus sentosus, in which an adult male devoured a juvenile. No reported cases were found in other species of the same genus, so we consider that this is the first report of cannibalism in Phyllodactylus.